1991
DOI: 10.1128/jb.173.2.514-520.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of Escherichia coli katE, which encodes catalase HPII

Abstract: A 3,466-bp nucleotide sequence containing the katE gene of Escherichia coli has been determined. An open reading frame of 2,259 bp was found and was preceded by a potential ribosome-binding site. The predicted N-terminal sequence agreed with the sequence determined by direct amino acid sequencing, and the predicted direction of transcription was confirmed by expression of the gene cloned in both directions behind a T7 promoter. The start site of transcription was determined to be 127 bp upstream from the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 43 publications
1
104
0
Order By: Relevance
“…Identities of greater than 50% were observed between KatX and catalases from bovine, maize, Listeria seeligeri (17), Lactobacillus sake (26), Pseudomonas syringae, and Bacillus subtilis (5). More importantly, all amino acid residues involved in the active site (i.e., His-128, Ser-167, and Asn-201 in KatE and His-89, Ser-128, and Asn-162 in KatX) and in heme binding (i.e., Val-127, Thr-168, Phe-206, and Phe-214 in KatE and Val-88, Thr-129, Phe-167, and Phe-175 in KatX on the distal side of the heme and Pro-393, Arg-411, and Tyr-415 in KatE and Pro-354, Arg-372, and Tyr-376 in KatX on the proximal side of the heme) were highly conserved (47).…”
Section: Localization Of Katxmentioning
confidence: 99%
See 2 more Smart Citations
“…Identities of greater than 50% were observed between KatX and catalases from bovine, maize, Listeria seeligeri (17), Lactobacillus sake (26), Pseudomonas syringae, and Bacillus subtilis (5). More importantly, all amino acid residues involved in the active site (i.e., His-128, Ser-167, and Asn-201 in KatE and His-89, Ser-128, and Asn-162 in KatX) and in heme binding (i.e., Val-127, Thr-168, Phe-206, and Phe-214 in KatE and Val-88, Thr-129, Phe-167, and Phe-175 in KatX on the distal side of the heme and Pro-393, Arg-411, and Tyr-415 in KatE and Pro-354, Arg-372, and Tyr-376 in KatX on the proximal side of the heme) were highly conserved (47).…”
Section: Localization Of Katxmentioning
confidence: 99%
“…The amino acid residues involved in binding these molecules (His-304 for binding the pyrophosphate group of NADPH and His-234, Lys-236, and Tyr-214 for binding water) have been established in bovine catalase. von Ossowski et al (47) studied differences in amino acid residues at the binding sites of these molecules in E. coli HPII (KatE) and other proteins. They found that the presence of Glu-362 in KatE in an analogous location to His-304 in bovine catalase made binding of the negatively charged pyrophosphate groups of NADPH to the negatively charged Glu-362 unlikely.…”
Section: Localization Of Katxmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains and Plasmids-The plasmid pAMkatE72 (22) was used as the source for the katE gene. Phagemids pKSϩ and pKSϪ from Stratagene Cloning Systems were used for mutagenesis, sequencing, and cloning.…”
Section: Methodsmentioning
confidence: 99%
“…HPI (encoded by katG) is a prokaryotic broadspectrum bifunctional peroxidase-catalase inducible by hydrogen peroxide (7). The E. coli catalase HPII (encoded by katE) is a monofunctional enzyme that has sequence similarities to eukaryotic catalase (17). Biochemical and serological characterizations of mycobacterial lysates have also identified two mycobacterial catalases (20).…”
mentioning
confidence: 99%